2012
DOI: 10.1371/journal.pone.0031763
|View full text |Cite
|
Sign up to set email alerts
|

AVPR1A and SLC6A4 Polymorphisms in Choral Singers and Non-Musicians: A Gene Association Study

Abstract: Amateur choral singing is a common pastime and worthy of study, possibly conferring benefits to health and social behaviour. Participants might be expected to possess musical ability and share some behavioural characteristics. Polymorphisms in genes concerned with serotonergic neurotransmission are associated with both behaviour and musical aptitude. Those investigated previously include the variable number tandem repeats RS1, RS3 and AVR in the AVPR1A (arginine vasopressin receptor 1a) gene and STin2 in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 54 publications
(72 reference statements)
0
37
0
1
Order By: Relevance
“…GALM encodes galactose mutarotase which is functioning in serotonin metabolism [48], [49]. Curiously, we and others have studied the association of the serotonin transporter (5-HTT) in music related phenotypes [16], [17], [19], [20], [50]. A duplication at 10q11.22 was found in 24% and a deletion at 3p22.2 in 20% of the creative phenotype subjects in two families each (families 14 and 17; families 13 and 17, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GALM encodes galactose mutarotase which is functioning in serotonin metabolism [48], [49]. Curiously, we and others have studied the association of the serotonin transporter (5-HTT) in music related phenotypes [16], [17], [19], [20], [50]. A duplication at 10q11.22 was found in 24% and a deletion at 3p22.2 in 20% of the creative phenotype subjects in two families each (families 14 and 17; families 13 and 17, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Until now, little evidence for the molecular genetic background of musical aptitude has been obtained. In the absence of such evidence, we and others have performed both genome wide analyses and candidate gene studies in musical traits [13], [15], [16], [17], [18], [19], [20]. Intriguingly, genome-wide analyses performed separately in Finnish and Mongolian populations with different music phenotypes (musical aptitude and musical ability) revealed linkage in the partly overlapping genetic regions at chromosome 4q [15], [18].…”
Section: Introductionmentioning
confidence: 95%
“…An earlier study of our own group has found a correlation between the onset of musical training, and the size of the motor cortex as indicated by the depth of the central sulcus (Amunts et al, 1997). This correlation provides an argument, that the human motor cortex can exhibit functionally induced long-lasting structural adaptations, probably at the background of a specific genetic predisposition (Theusch and Gitschier, 2011; Morley et al, 2012; Park et al, 2012; Ukkola-Vuoti et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Singers have also been the topic of studies into the presence or absence of the AVPR1a and SLC6A4 polymorphisms. Gene association with choral singing has been documented (Morley et al, 2012). Researchers have also found evidence of association between tests of musical aptitude and the AVPR1a haplotypes (Ukkola, Onkamo, Raijas, Karma, & Järvelä, 2009).…”
Section: Genetic Expression and Performing Artsmentioning
confidence: 98%